Perceived physical ability in competitive swimming. - A. Salguero; R. González-Boto; C. Tuero; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
The Perceived Physical Ability Scale by Ryckman et al. (1982) has been used to measure individual perception of physical ability in young competitive swimmers. 428 swimmers of different competitive categories participated in this study. The group consisted of 204 males and 224 females with a mean age of 14 years. Results indicate that males rated higher in general and total perceived ability. To a lesser extent, general and total perceived ability decreased from younger to older swimmers. Similar results were obtained for competitive level or years of experience. It is concluded that physical perceived ability scales, mainly those including swimming specific items, are an adequate instrument to predict real ability of swimmers, provided that athletes of equivalent level and characteristics are studied. KEY WORDS: Perceived physical ability, swimming, gender, age